Giant vesicles from rehydrated crude mixtures containing unexpected mixtures of amphiphiles formed under plausibly prebiotic conditions. Issue 19 (3rd May 2017) - Fiore, Michele; Madanamoothoo, Warren; Berlioz-Barbier, Alexandra; Maniti, Ofelia; Girard-Egrot, Agnès; Buchet, René; Strazewski, Peter
Abstract : Giant lipid vesicles resemble compartments of biological cells, mimicking them in their dimension, membrane structure and partly in their membrane composition. Abstract : Giant lipid vesicles resemble compartments of biological cells, mimicking them in their dimension, membrane structure and partly in their membrane composition. The spontanenous appearance of closed membranes composed of bilayers of self-assembling amphiphiles was likely a prerequisite for Darwinian competitive behavior to set in at the molecular level. Such compartments should be dynamic in their membrane composition (evolvable), and sufficiently stable to harbor macromolecules (leak-free), yet semi-permeable for reactive small molecules to get across the membrane (stay away from chemical equilibrium). Here we describe bottom-up experiments simulating prebiotic environments that support the formation of simple amphiphilic molecules capable of self-assembling into vesicular objects on the micrometer scale. Long-chain alkyl phosphates, together with related amphiphilic compounds, were formed under simulated prebiotic phosphorylation conditions by using cyanamide, a recognized prebiotic chemical activator and a precursor for several compound classes. Crude dry material of the thus obtained prebiotic mixtures formed multilamellar giant vesicles once rehydrated at the appropriate pH and in the presence of plausibly prebiotic co-surfactants, as observed by optical microscopy. The size and the shape of lipid aggregates tentatively suggest that prebiotic lipid assemblies could encapsulate peptides or nucleic acids that could be formed under similar chemical prebiotic conditions. The formation of prebiotic amphiphiles was monitored by using TLC, IR, NMR and ESI-MS and UPLC-HRMS. In addition we provide a spectroscopic analysis of cyanamide under simulated prebiotic conditions in the presence of phosphate sources and spectroscopic analysis of O -phosphorylethanolamine as a plausible precursor for phosphoethanolamine lipids.